How do you find the equation of the tangent line to the curve #f(x) = (x-1)^3# at the point where x = 2?
y = 3x - 5
To find the equation in the form y = mx + c , where m represents the gradient and c, the y-intercept. The value of f'(2) will give m and f(2) will assist in finding c.
partial equation of tangent is y = 3x + c , and using (2,1 )
gives : 1 =3(2) + c → c = - 5
thus equation of tangent is : y = 3x - 5
By signing up, you agree to our Terms of Service and Privacy Policy
To find the equation of the tangent line to the curve f(x) = (x-1)^3 at the point where x = 2, we need to find the slope of the tangent line and the coordinates of the point of tangency.
First, we find the derivative of f(x) with respect to x, which gives us f'(x) = 3(x-1)^2.
Next, we substitute x = 2 into f'(x) to find the slope of the tangent line at x = 2. This gives us f'(2) = 3(2-1)^2 = 3.
Now, we have the slope of the tangent line, which is 3, and the point of tangency, which is (2, f(2)). To find f(2), we substitute x = 2 into f(x), giving us f(2) = (2-1)^3 = 1.
Therefore, the point of tangency is (2, 1), and the slope of the tangent line is 3.
Using the point-slope form of a linear equation, y - y1 = m(x - x1), where (x1, y1) is the point of tangency and m is the slope, we can substitute the values to find the equation of the tangent line.
Substituting (2, 1) for (x1, y1) and 3 for m, we have y - 1 = 3(x - 2).
Simplifying this equation gives us the equation of the tangent line to the curve f(x) = (x-1)^3 at the point where x = 2: y = 3x - 5.
By signing up, you agree to our Terms of Service and Privacy Policy
To find the equation of the tangent line to the curve ( f(x) = (x-1)^3 ) at the point where ( x = 2 ), follow these steps:
- Find the derivative of ( f(x) ) using the power rule: ( f'(x) = 3(x-1)^2 ).
- Evaluate ( f'(2) ) to find the slope of the tangent line at ( x = 2 ): ( f'(2) = 3(2-1)^2 = 3 ).
- Use the point-slope form of the equation of a line: ( y - y_1 = m(x - x_1) ), where ( (x_1, y_1) ) is the point of tangency and ( m ) is the slope.
- Substitute ( x_1 = 2 ), ( y_1 = f(2) ), and ( m = f'(2) ) into the point-slope form equation.
- Simplify the equation to find the tangent line's equation.
Therefore, the equation of the tangent line to the curve ( f(x) = (x-1)^3 ) at the point where ( x = 2 ) is ( y - 1 = 3(x - 2) ).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you find the slope of a tangent line to the graph of the function# f(x)= -5/x^3# at x=9?
- Is there a certain formula for derivatives?
- How do you find the equation of the tangent line #y=x-lnx# at #(e, e-1)#?
- How do you use the definition of a derivative function to calculate f'(4) where #f(x) = x+3#?
- Find all points on the curve #x^2y^2+xy=2# where the slope of the tangent line is #-1#?
![Answer Background](/cdn/public/images/tutorgpt/ai-tutor/answer-ad-bg.png)
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7